2021
DOI: 10.2991/aebmr.k.210416.018
|View full text |Cite
|
Sign up to set email alerts
|

The Consumer Behavior Among Muslim Millennials in Buying Sharia Stock in the City of Kudus

Abstract: The urgency of public education from saving society to investing society is needed at this time to increase interest in investing. This research is to determine whether consumer behavior (halal knowledge, Islamic religiosity, financial technology, and risk) on the Buying of Sharia Stock. The design of this study is quantitative. The population and sample involved in the research are the millennial generation of Muslims in the city of Kudus. Sampling in this study using purposive sampling technique. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Moreover, Cahya et al revealed that Islamic religiosity was not a significant factor for purchasing sharia stock. This study further highlighted that some people were aware of sharia laws but chose not to follow them [1].…”
Section: B Studies Showing Religiosity As Not Anmentioning
confidence: 80%
See 2 more Smart Citations
“…Moreover, Cahya et al revealed that Islamic religiosity was not a significant factor for purchasing sharia stock. This study further highlighted that some people were aware of sharia laws but chose not to follow them [1].…”
Section: B Studies Showing Religiosity As Not Anmentioning
confidence: 80%
“…It also showed that there were individuals who understood the sharia rules but did not implement them. Therefore, risk and Islamic religiosity did not have any major consideration in buying sharia stock [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation